2008
DOI: 10.1159/000143795
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin Detection in the Sputum/Saliva for the Diagnosis of Gastroesophageal Reflux Disease in Patients with Clinically Suspected Atypical Gastroesophageal Reflux Disease Symptoms

Abstract: Background/Aims: Atypical manifestations of gastroesophageal reflux disease (GERD) are diverse. We aimed to determine whether pepsin detection in the sputum/saliva could be useful for diagnosing GERD in patients with clinically suspected atypical GERD symptoms. Methods: Patients with clinically suspected atypical GERD symptoms provided sputum/saliva collected before bedtime, at the time of those symptoms, and after awakening for pepsin measurement by Western blot analysis. All subjects received 24-hour esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 48 publications
2
64
0
2
Order By: Relevance
“…An immunoserologic test was used similar to the latter study. Another study reports a sensitivity of 89% and a specificity of 68% in a salivary pepsin western blot analysis (26). Other relevant studies also recommend pepsin as a diagnostic marker (27,28).…”
Section: Discussionmentioning
confidence: 96%
“…An immunoserologic test was used similar to the latter study. Another study reports a sensitivity of 89% and a specificity of 68% in a salivary pepsin western blot analysis (26). Other relevant studies also recommend pepsin as a diagnostic marker (27,28).…”
Section: Discussionmentioning
confidence: 96%
“…Although 24-hour esophageal pH monitoring has been regarded as the gold standard test for diagnosing GERD, it may not be sensitive because of day-to-day variability in symptom occurrence, inability to do normal activities due to an inserted nasal catheter, no detection of gastric contents aspirated into the lung and oropharynx, and no measurement of non-acid reflux. Actually, it has recently been shown that 24-hour pH-metry results are not well correlated with PPI test results, particularly in patients suspected to have atypical GERD symptoms [18]. Evaluation by impedance pH monitoring or 48- or 72-hour catheterless pH monitoring might compensate for these drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in adults have correlated 24-hour pH monitoring results with the detection of pepsin in saliva or sputum, the authors concluding that pepsin detection was indicative of proximal GER [15,16]. Furthermore, Little et al [17] stated that any reflux to the hypopharynx was significant in patients with respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%